New Jurassic Hangingflies (Insecta: Mecoptera: Bittacidae) from Inner Mongolia, China - Liu, Sulin; Shih, Chungkun; Bashkuev, Alexei; Ren, Dong (Zootaxa, 2016)
A new bittacid genus, Composibittacus gen. nov., with two new species, C. bipunctatus gen. et sp. nov. and C. reticulatus sp. nov., and a new species of Orthobittacus Willmann 1989, O. maculosus sp. nov., are described from the latest Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China. Composibittacus gen. nov. has unique wing characters, such as five pterostigmal crossveins between R1 and R2 and R1 and R2+3 and an elongated pterostigma area, which distinguishes it from all other known genera in Bittacidae. Orthobittacus maculosus sp. nov. differs from other species of Orthobittacus by a combination of the following wing characters: M with six branches in forewings and hind wings, two crossveins between C and Sc, and two pterostigmal crossveins in the forewing. In addition, O. maculosus sp. nov. has light-colored or white spots on the fore- and hind wings. These new venational characters of Composibittacus gen. nov. and O. maculosus sp. nov. enhance our understanding of the diverse morphological characters of early hangingflies. Furthermore, based on the striking similarity of the wings of O. maculosus sp. nov. and Juracimbrophlebia ginkgofolia Wang, Labandeira, Shih & Ren 2012 (Cimbrophlebiidae), we propose that leaf mimesis and mutualism with ginkgo plants might have been present in the Bittacidae, as has been proposed in the Cimbrophlebiidae.